(untitled) (Baghdad Science Journal, 2007)
This study was conducted in Animal Resources Department , College of Agriculture to estimate the effect of chemical and biological treatments to improve the nutritive value of poor quality roughages ( corn cobs and wild reed ) . The feeds were treated chemically with 4% NaoH solution ,whereas Aspergillus niger was used to ferment corn cobs and wild reed samples . The chemical analysis showed that protein percentages of corn cobs and wild reed was increased significantly (P